Improving the habits of mind of senior high school students toward biology learning through creative problem-solving learning model based on mind mapping: Pre-experimental study - Nukhbatul Bidayati Haka; Khairun Nisa; Hardiyansyah Masya (Assimilation: Indonesian Journal of Biology Education, 2022)
There have been many attempts to improve the habits of mind of high school students in Biology through various learning models. However, only a few research results show efforts to improve students' habits of mind through the creative problem solving learning model with mind mapping techniques. Therefore, the purpose of the study was to determine the effect of the creative problem solving learning model with mind mapping techniques on increasing the habits of mind of high school students in learning biology. The pre-experimental method was used with the one group pretest-posttest design. Involving three research classes with 108 students taken by cluster random sampling and getting the same treatment using the creative problem solving learning model with mind mapping techniques. Research data collection uses essay and habits of mind questionnaires. The implication of this research is to increase students' habits of mind. students become accustomed to using their minds critically, creatively and able to control themselves very well as evidenced by an increase in posttest scores on essay tests and habits of mind questionnaires with an average of 86% and 83% (very good) with an average N-Gain 66% and 52% (medium), so the creative problem solving learning model was recommended to increase the habits of mind of high school students in biology learning.